A promising approach to scale up health care improvements in low-and middle-income countries: the wave-sequence spread approach and the concept of the slice of a system - Massoud, M. Rashad; Mensah-Abrampah, Nana (F1000Research, 2014)
There are several examples of successes in improving health care. However, many of these tend to remain limited to the sites they were originally developed in. There are fewer examples of successes that have spread to the remainder of the systems they were developed in. This article discusses the wave-sequence approach, which is a type of spread focusing on spreading in a systematic, sequential manner, using spread agents—people who participated in the original demonstration sites—to spread to other parts of the systems. The paper also discusses the associated concept of the “slice” of a system. In addition, we describe a phenomenon related to the rate of adoption that we are seeing in the wave-sequence approach.